2022
DOI: 10.1101/2022.09.29.510081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical somatostatin interneuron subtypes form cell-type specific circuits

Abstract: The cardinal interneuron classes are a useful simplification of cortical interneuron diversity, but such broad subgroupings glosses over the molecular, morphological, and circuit specificity of interneuron subtypes, most notably among the somatostatin interneuron class. The organizing principles by which the connectivity of these subtypes is specified are unknown. To address this knowledge gap, we designed a series of genetic strategies to target the breadth of somatostatin interneuron subtypes. Using these st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 65 publications
5
21
3
Order By: Relevance
“…For example, ET cells received inputs from a greater number and diversity of inhibitory cell types than layer 5 IT or NP cells. This large population of highly selective inhibitory cell types, consistent with recent observations of transcriptomically-defined SST neurons 36 , could allow for more complex regulation of these key cortical outputs compared to other layer 5 cells. Most M-types received input from multiple motif groups, suggesting there could be network conditions when different combinations of excitatory subpopulations controlled together as part of a shared circuit.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…For example, ET cells received inputs from a greater number and diversity of inhibitory cell types than layer 5 IT or NP cells. This large population of highly selective inhibitory cell types, consistent with recent observations of transcriptomically-defined SST neurons 36 , could allow for more complex regulation of these key cortical outputs compared to other layer 5 cells. Most M-types received input from multiple motif groups, suggesting there could be network conditions when different combinations of excitatory subpopulations controlled together as part of a shared circuit.…”
Section: Discussionsupporting
confidence: 85%
“…A principle concern is the generalizability of data, which comes from a single animal, is located toward the edge of VISp, and has at most a few examples per cell type. Concurrent work in the same dataset has found that morphologically-defined cell types show consistent target preferences 85 , and our data also agrees with recent functional measurements of type-specific connectivity of SST cells 36 . We thus believe that the connectivity results will apply generally, although it will be important to measure the variability across individual cells, distinct animals, and locations in cortex.…”
Section: B Limitationssupporting
confidence: 91%
See 2 more Smart Citations
“…We focused on Martinotti cells (MCs) in layers 4 and 5 (L4, L5), which have distinct morphological features 23,31,32 , are known to be somatostatin positive (Sst+) 24,25 , and span six Sst+ MET-types 21 . Additionally, previous functional studies suggest that MCs may connect broadly in a 'blanket of inhibition' [33][34][35] or inhibit a subset of excitatory targets within and across cortical layers 32,[36][37][38][39] . Finally, in a concurrent study 40 individual MCs are found to preferentially target different excitatory cell types, however, it remains unknown whether Sst-MET-types have distinct synaptic connectivity profiles especially as morphologically similar neurons can have distinct connectivity profiles 41 .…”
Section: Introductionmentioning
confidence: 99%